Oceans governance in the twenty-first century managing the blue planet - Haward, M. G. (Marcus G.); Vince, Joanna (Edward Elgar, 2008)
Oceans Governance in the Twenty-first Century analyses the development of national, regional and international initiatives and arrangements directed towards governance of the world's seas and oceans.